Inoculação de raízes destacadas de variedades de mandioca, com resposta diferencial de campo à podridão de raízes de Fusarium solani - FÉLIX, João Paulo da Silva (Universidade Federal do Oeste do Pará, 2021)
In the process of selecting sources of resistance to cassava root rot, it is fundamental to establish efficient methodologies. Currently, the test in highlighted roots is the main method applied by breeding programs in the search for resistant genotypes, however, some results do not correspond to field resistance. Therefore, the objective of this work was to validate the method of inoculation in roots for differentiation of varieties of cassava from the western region of Pará, regarding dry rot and to determine the variability in the pathogenicity of F. solani. For this, four experiments were conducted in a completely randomized factorial using the 'Amarelhinha' (resistant) and 'Bem-te-vi' (susceptible) varieties, considering the phenological stages of six (Amazonian summer), fourteen (Amazonian winter) and Eighteen months (Amazonian summer) and an experiment evaluating variations in the diameter of the drilling at inoculation. Initially, the roots were treated with sodium hypochlorite solution (200 ppm) for 2 minutes, while in the 14-month roots additional treatment with 490 ppm of thiophanate methyl fungicide suspension was carried out. As inoculum cultures were used in carrot-agar medium of five isolates of F. solani obtained from cassava root rot. The inoculations were performed by inserting discs with fungal structures into perforations that removed the shell in the proximal and distal thirds of the root, the central perforation served as control. The roots were then kept in a humid chamber at room temperature for 10 days, when the roots were cut and the depth and width of the lesions were evaluated in the pulp. The lesions varied from rounded to "V" shaped and fungicide pretreatment was efficient in controlling field infections and did not interfere either in the occurrence or in the shape of lesions in the evaluation at 14 months. The depth and width of the lesions presented an opposite response to the ages of the roots, the greater the age, the greater the depth and the smaller the width of the lesion, and vice versa. The time of root acquisition associated with the Amazonian summer and winter periods was not significant in the size of the lesions. In general, the 'Bem-te-vi' variety showed smaller lesions than 'Amarelinha', which limited the detection of races of the pathogen, for dry rot. The isolates had different levels of aggressiveness, with one group independent and the other dependent on the age of the roots. The diameter of the perforation for the inoculation interfered in the depth of the lesions, but did not alter the response of the varieties. Thus, the post-harvest resistance of the varieties did not correspond to the field strength in any of the experiments.